2022
DOI: 10.5539/jel.v11n3p47
|View full text |Cite
|
Sign up to set email alerts
|

Teaching in Tough Times: Examining EFL Teachers’ Perceptions of Online Learning Challenges in the Context of Higher Education in Saudi Arabia

Abstract: The global spread of online learning is noticeable and has further expanded due to the COVID-19 pandemic. Although this mode of learning is effective, several concerns have been raised by teachers. This qualitative study aimed to explore English as a Foreign Language (EFL) teachers’ perceptions of the online learning environment in order to uncover the challenges they face while teaching online. To achieve this objective, semi-structured interviews were conducted with 25 EFL teachers from the Prepara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…These findings can be said to correlate with several other studies in the related literature (e.g., Janke et al, 2021;Mata, 2021;Sharma et al, 2021). For example, in a study conducted by Saleh and Meccawy (2022), it was stated that cheating and plagiarism was a major problem for educators in higher education as it was considered all too easy to cheat in online environments. These studies also demonstrated that students found it easy to cheat during online exams; therefore, they were not motivated to attend, participate, or learn in their online lessons (Baniamer & Muhamed, 2022), and this resulted in increased instances of academic dishonesty (Mata, 2021;Surahman & Wang, 2022;Tarigan et al, 2021).…”
Section: Discussionsupporting
confidence: 78%
“…These findings can be said to correlate with several other studies in the related literature (e.g., Janke et al, 2021;Mata, 2021;Sharma et al, 2021). For example, in a study conducted by Saleh and Meccawy (2022), it was stated that cheating and plagiarism was a major problem for educators in higher education as it was considered all too easy to cheat in online environments. These studies also demonstrated that students found it easy to cheat during online exams; therefore, they were not motivated to attend, participate, or learn in their online lessons (Baniamer & Muhamed, 2022), and this resulted in increased instances of academic dishonesty (Mata, 2021;Surahman & Wang, 2022;Tarigan et al, 2021).…”
Section: Discussionsupporting
confidence: 78%
“…Another element to analyze is that teaching a foreign language presents unique challenges, which can lead EFL students to resort to fraud due to linguistic competence issues, academic writing challenges, time limitations, and lack of confidence [ 34 ]. Finally, time constraints, inadequate paraphrasing skills, and pressure to achieve good grades [ 35 ], along with technological advancements and COVID-19, have heightened academic dishonesty [ [41] , [42] , [43] , [44] , [45] ].…”
Section: Discussionmentioning
confidence: 99%
“…Saleh and Meccawy [ 43 ] examined the EFL instructors challenges in teaching online, emphasizing students' lack of motivation and participation and the need for stricter disciplinary policies to combat cheating. COVID-19 forced a swift transition to online classes, resulting in increased academic dishonesty as students have easier access to notes, the Internet, and assistance from peers or services like Chegg during virtual evaluations [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the biggest problems that stands as an obstacle to the goal of increasing the opportunities for individuals to choose in technical and vocational education is that this type of education was designed to serve secondary professions and secondary opportunities first, and therefore most of its pioneers attend it because they have not found anything else, or because they have found in it an initial guarantee of obtaining a profession (Saleh & Meccawy, 2022). Due to the dire need for its graduates, especially the education provided by public vocational and technical education institutions and its graduates who also work in public institutions .…”
Section: Literature Reviewmentioning
confidence: 99%